Survey of software assurance - FANG Bin-xing1; LU Tian-bo2; LI Chao1 (Tongxin xuebao)
Firstly,various definitions of software assurance were discussed,the key properties of software assurance were summarized,and the software assurance model S3R（security,safety,reliability,survivability） was proposed to describe the discipline of software assurance.Then,the software assurance programs of DHS,DOD and NASA were highly in-troduced as well as S3R development.Finally,the software assurance standards-setting was specified and the develop-ment trends of software assurance research were pointed.